Analisis senyawa kimia dan uji antihiperglikemia daun petai cina (Leucaena leucocephala) dari kawasan geotermal Ie Seum Aceh Besar - Noni Zakiah; Munira Munira; Berwi Fazri Pamudi; Muhammad Nasir; Frengki Frengki; Halimatussakdiah Halimatussakdiah (Poltekkes Kemenkes Aceh, 2024)
Background: Hyperglycemia can cause serious complications due to the side effects of synthetic drugs used. Traditional medicines, such as petai cina, which contain secondary metabolite compounds like flavonoids, saponins, and steroids, have antidiabetic potential.Objectives: Hyperglycemia can cause serious complications due to the side effects of synthetic drugs used. Traditional medicines, such as petai cina, which contain secondary metabolite compounds like flavonoids, saponins, and steroids, have antidiabetic potential.Methods: This experimental research used a Completely Randomized Design (CRD) with 11 treatments: Na CMC, glibenclamide, and ethanol, ethyl acetate, and N hexane extracts of petai cina leaves at doses of 200 mg/kg BW, 400 mg/kg BW, and 600 mg/kg BW each. Each treatment was repeated five times.Results: Phytochemical screening showed that petai cina leaf extract contains phenolics, flavonoids, steroids, and saponins. GC-MS tests identified antidiabetic compounds such as phytol, squalene, and octacosanol. The antihyperglycemic test showed a significant decrease in blood sugar levels in rats after administration of petai cina leaf extract (P = 0,00). The decrease in blood sugar levels increased over time after the extract was given.Conclusion: Chinese petai leaf extract sourced from the Ie Seum Aceh Besar geothermal area exhibits an antihyperglycemic effect on male rats. KeywordsAntihyperglycemic, Leucaena leucocephala, geothermal, Diabetes, Traditional medicine